Long-term effects and complication rates of Coonrad-Morrey total elbow arthroplasty - a retrospective analysis of 95 prostheses in 16-year follow-up - Miika Stenholm; Hannu Tiusanen; Pjotr Sarantzin; Timo Lindström; Mikhail Saltychev (MedCrave Group, 2022)
Objectives: To investigate long-term effects and complication rates after Coonrad-Morrey semi-constrained total elbow replacement.
Methods: Retrospective analysis of consecutive Coonrad-Morrey total elbow arthroplasties performed in 1995–2006.
Results: The mean Mayo elbow score was 47.0 (SD 21.9) points preoperatively and 87.0 (SD 13.7) at the end of 16-year follow-up (p<0.001). The respective figures for mean pain in motion were 6.1 (SD 2.8) and 0.7 (SD 1.9) points (p<0.001). At the end of follow-up, the average extension lag was 30°, flexion 135°, pronation 67°, and supination was 74°. The complication rate was 19%.
Conclusion: Semi-constrained linked Coonrad-Morrey total elbow arthroplasty displayed promising clinical results and a long-lasting satisfaction in the surgery results. In the 16-year follow-up, there were 12 periprosthetic fractures and the overall complication rate was 19%.
Keywords: Semi-constrained elbow arthroplasty, Coonrad- Morrey total elbow arthroplasty, Elbow Arthroplasty, Rheumatoid Arthritis and elbow arthroplasty